Pediatric radiation oncology - Halperin, Edward C. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Pediatric Radiation Oncology is the definitive text and reference on use of radiation therapy for childhood cancer. The fifth edition reviews all significant recent clinical trials--including, for the first time, significant European clinical trials--and provides increased coverage of international and Third World issues. The latest cancer staging guidelines are included. New chapters cover psychosocial aspects of radiotherapy for the child and family and medical management of pain, nausea, nutritional problems, and blood count depression in the child with cancer"--Provided by publisher.